The power of regional heritability analysis for rare and common variant detection: simulations and application to eye biometrical traits - Uemoto, Yoshinobu; Pong-Wong, Ricardo; Navarro, Pau; Vitart, Veronique; Hayward, Caroline; Wilson, James F.; Rudan, Igor; Campbell, Harry; Hastie, Nicholas D.; Wright, Alan F.; Haley, Chris S. (Frontiers in Genetics, 2013)
Genome-wide association studies (GWAS) have provided valuable insights into the genetic basis of complex traits. However, they have explained relatively little trait heritability. Recently, we proposed a new analytical approach called regional heritability mapping (RHM) that captures more of the missing genetic variation. This method is applicable both to related and unrelated populations. Here, we demonstrate the power of RHM in comparison with single-SNP GWAS and gene-based association approaches under a wide range of scenarios with variable numbers of quantitative trait loci (QTLs) with common and rare causal variants in a narrow genomic region. Simulations based on real genotype data were performed to assess power to capture QTL variance, and we demonstrate that RHM has greater power to detect rare variants and/or multiple alleles in a region than other approaches. In addition, we show that RHM can capture more accurately the QTL variance, when it is caused by multiple independent effects and/or rare variants. We applied RHM to analyze three biometrical eye traits for which single-SNP GWAS have been published or performed to evaluate the effectiveness of this method in real data analysis and detected some additional loci which were not detected by other GWAS methods. RHM has the potential to explain some of missing heritability by capturing variance caused by QTL with low MAF and multiple independent QTLs in a region, not captured by other GWAS methods.